THE IMPLEMENTATION OF SCIENCE INQUIRY-BASED WEBSITE ORIENTED BY CULTURAL DEVIANCE SOLUTION TO INSTILL STUDENTS’ CHARACTER AND INDEPENDENCE (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
This research aims to determine the influence of science learning website oriented by cultural deviance solution (CDS) based on inquiry to grow students’ character and independence on the learning material theme of Classification. This research design is Posttest Only Control Design by using Cluster Random Sampling technique to draw the sample. Based on the results of data analysis, it can be concluded that the website was effective to be used to instill students’ character and independence.